2020
DOI: 10.1186/s13287-020-01597-8
|View full text |Cite
|
Sign up to set email alerts
|

Prospective isolation of chondroprogenitors from human iPSCs based on cell surface markers identified using a CRISPR-Cas9-generated reporter

Abstract: Background: Articular cartilage shows little or no capacity for intrinsic repair, generating a critical need of regenerative therapies for joint injuries and diseases such as osteoarthritis. Human-induced pluripotent stem cells (hiPSCs) offer a promising cell source for cartilage tissue engineering and in vitro human disease modeling; however, off-target differentiation remains a challenge during hiPSC chondrogenesis. Therefore, the objective of this study was to identify cell surface markers that define the t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 66 publications
2
36
0
Order By: Relevance
“…10 A similar pattern of TRPV4 expression has also been observed in human induced pluripotent stem cells (iPSCs), mesenchymal stem cells (MSCs), and adipose stem cells (ASCs) undergoing chondrogenesis. [25][26][27][28] Furthermore, ASCs isolated from Trpv4 À/À mice exhibit reduced chondrogenic differentiation potential and enhanced osteogenic potential compared to ASCs from Trpv4 +/+ mice. 29 Interestingly, the chemical activation of TRPV4 induced Sox9-dependent reporter activity, 10 and iPSCs derived from patients with a lethal skeletal dysplasia caused by TRPV4 mutation show significantly decreased chondrogenesis and expression of COL2A1, SOX9, ACAN, type X collagen (COL10A1), and runt-related protein 2 (RUNX2).…”
Section: Introductionmentioning
confidence: 99%
“…10 A similar pattern of TRPV4 expression has also been observed in human induced pluripotent stem cells (iPSCs), mesenchymal stem cells (MSCs), and adipose stem cells (ASCs) undergoing chondrogenesis. [25][26][27][28] Furthermore, ASCs isolated from Trpv4 À/À mice exhibit reduced chondrogenic differentiation potential and enhanced osteogenic potential compared to ASCs from Trpv4 +/+ mice. 29 Interestingly, the chemical activation of TRPV4 induced Sox9-dependent reporter activity, 10 and iPSCs derived from patients with a lethal skeletal dysplasia caused by TRPV4 mutation show significantly decreased chondrogenesis and expression of COL2A1, SOX9, ACAN, type X collagen (COL10A1), and runt-related protein 2 (RUNX2).…”
Section: Introductionmentioning
confidence: 99%
“…For example, using the approach of single-cell analysis, Dicks et al . ( 35 ) have found that at least nine different cell clusters—including chondrogenic, neurogenic, and other nonbone/noncartilage mesenchymal cells—are identified in hiPSC-derived mesodermal chondrocyte culture. Similarly, Umeda et al .…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the conditions that differentiate PSCs toward cells that bear more chondrocytic properties, PSCs in which chondrocyte‐specific reporter constructs were integrated have been investigated. The promoter/enhancer sequences of type XI collagen α2 chain gene ( COL11a2 ) (Yamashita et al., 2015) or COL2A1 (Adkar et al., 2019; Dicks et al., 2020) have been used to direct the reporter expression in a chondrocyte‐specific manner. To increase the efficiency of the chondrocytic differentiation, the transfection of non‐viral vectors containing TGFβ3 and BMP2 to promote the chondrogenic differentiation of PSCs (Rim et al., 2020) and lithium‐containing biomaterial to reduce hypertrophy (Hu et al., 2020) have also been applied.…”
Section: Protocols For Deriving Chondrocytes From Human Pscsmentioning
confidence: 99%